Foreign and Domestic University Students Assess the Threat Of COVID-19 Differently: Experience from Lockdown Period - Evgeni NIKOLAEV; Denis HARTFELDER; Elena LAZAREVA; Ekaterina VASILEVA; Rahmatulla YAKUBOV; Ahmed GAFAROV (Communications of International Proceedings, 2021)
The purpose was to study the specifics of assessing the COVID-19 threat in foreign and domestic students of a Russian university. It took place in May 2020, when university students had a distant form of learning. The study involved 304 foreign and 164 domestic students who completed an anonymous online survey. Foreign students showed more anxiety about their future. They were more interested in information about COVID-19, and more closely observed restrictive measures. They were also more likely to report significant disruption to their plans and threats to material well-being and were less optimistic about the future in the context of such pandemics. The results can be used in developing prevention programs.
Keywords: COVID-19; pandemic; threat; foreign students; domestic students; Ulianov Chuvash State University